Proceedings of the National scientific workshop evaluation of effects of mangrove reforestation on the environment and coastal local life in JRC funded project areas (Agricultural Publishing House, 2003)
Mangrove are a highly productive ecosystem in estuarine and coastal areas. They offer habitats to economically valuable aquatic animals, feeding and breeding grounds for many species's larvae, including shrimps and crabs. On the other hand, mangroves play a very essential role in the protection of coastal environment, limiting erosion, pollution and assisting the expansion of continental shelf,...